RISK FACTORS FOR THE OCCURRENCE AND DEVELOPMENT OF ENDO-PERIODONTAL LESIONS - Anamaria Zaharescu; Liana Aminov; Amelia-Elena Surdu; Odette-Elena Luca; Irina-Georgeta Sufaru; Liliana Pasarin; Georgiana Laza-Demirbuken; Raluca Mocanu; Diana Anton; Silvia Martu (Romanian Dental Association for Education, 2019)
Understanding the interaction between endodontic and periodontal lesions is of crucial importance to the clinician because of the challenges commonly encountered in the evaluation, diagnosis, treatment and prognosis of these combined diseases. Among the risk factors for the occurrence and development of endo-periodontal lesions are: incorrect endodontic treatment, lack of coronary seal in coronary restorations, occlusal trauma, radicular resorption of infectious or non-infectious nature, peripheral perforations within the endodontic treatment or dental malformations. The treatment and prognosis of endo-periodontal lesions varies depending on the etiology, pathogenesis and the correct recognition of each specific condition.